An Analysis of the Outcomes of Language Contacts: with Specials Reference to Arabi-Malayalam - Cheerangote, Sayed Saidalavi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Until the 20th century, the AM script was extensively used to teach religious literature and for creative expressions among Mappilas (Muslims in Malabar) in Kerala. Most of the Mappila songs were written in AM script. The literary tradition of Mappila Muslims of Malabar is evident in the AM literature that includes Romantic Ballads, Folk Tales and Battle Songs. AM periodicals had an important role in the social reformation of the Mappilas. Several periodicals were published in AM language to preach the basic tenets of Islam to the commoners and to make them aware of the evil practices and superstitions existed in those days. This study treats AM as a contact language and it aims at isolating the contact induced elements in AM. The empiric foundation of the present study is the extensive data collected from AM literature representating different period and from different genres. The works used for data collection were Mohiyudheen Maala (1607 A D), Nool Maduhu (1737 AD), The Padappattu (War Songs) of Moyeen Kutty Vaidyar (1852AD to 1892 AD), and Chaar Dharwesh (1883 AD). The results of this study indicate that there are various borrowing patterns of grammar that occur in ARABI-MALAYALAM language contacts such as; Coordinating Conjunctions, Number Markers, Adjectives etc.